قاعدة " كل تصرف تقاعد عن تحصيل مقصوده فهو باطل " : وأثرها في العقود المالية - ديرشوي، سمية عبد الله (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2022)
This thesis aims to study the maxim, which says, “Any disposition that does not fulfill its objective is void.” According to all jurists, it is an original jurisprudential maxim, although to varying degrees among them. This maxim is shrouded with ambiguity in terms of the types of dispositions and objectives it includes, its boundaries, the parameters that determine the disposition's objective, the impediments that may prevent the dispositions from achieving their objectives, and the effect of the maxim on financial transactions. Hence, to clarify all the mentioned points, there is a need to conduct a comprehensive and in-depth study of the maxim, applying it to three financial transactions: (joint-stock companies, organized tawarruq, and margin trading). The significance of this study lies in its explanation of a comprehensive legal maxim. Jurists have agreed on the validity and implementation of the maxim in the various chapters of jurisprudence (fiqh). The study followed the descriptive and analytical approaches by collecting the necessary data related to the study, including explanations, definitions, and applications, in order to reach the results. Among the most important findings, this maxim is supported by evidence that indicates that contradicting what is intended by Shari'ah is invalid. The link between the maxim and the conditions that prevent a disposition from fulfilling its intended Shari'ah objective means that if one of the conditions for the validity of the contract is missing, or a contractual stipulation contradicts the objective of the disposition, then the stipulation is void and the disposition is also void. Moreover, the link between the under-researched maxim and the principle of "blocking lawful means that lead to unlawful ends" and legal tricks manifest in the means that prevent the disposition from achieving its intended objective because the disposition does not fulfill the objective for which it was legislated, thus, such disposition becomes void and is given no legal consideration. The thesis has covered several applications of this maxim; among them are organized tawarruq, joint-stock companies, and margin trading. This thesis has shown the Shariah violations that are contained in these contracts.